(untitled) (Milli Mála, 2015)
Phraseology (German Phraseologie, Icelandic fraseólógía) is an important area of linguistics and of great interest especially in the acquisition of foreign languages. The paper aims to describe the most important characteristics of word groups (feste Wortverbindungen/föst orðasambönd) like phraseologisms, phraseological units, and idioms as well as their classification in German and Icelandic. The paper is based on the theoretical background of German phraseology, primarily the research of Harald Burger and his definitions of the characteristics, structure and essential terms of phraseology. The paper presents characteristics such as Polylexikalität, Festigkeit, Idiomatizität, Motiviertheit, Idiomatisierung along with discussions of the Icelandic equivalent terms. An overview is given of Harald Burger’s classification of Phraseologismen into three categories: referentielle Phraseologismen/tilvísandi föst orðasambönd, strukturelle Phraseologismen/formgerðarleg föst orðasambönd and kommunikative Phraseologismen/samskiptabundin föst orðasambönd with their subcategories. German and Icelandic examples of various types of phraseologisms such as Idiome/orðtök, Sprichwörter/málshættir, Kollokationen/ orðastæður, Geflu?gelte Worte/fleyg orð and Vergleiche/fastar líkingar are presented. Hopefully the result of this study will be to strengthen the discussion of phraseology in Iceland.